2021
DOI: 10.5304/jafscd.2021.102.033
|View full text |Cite
|
Sign up to set email alerts
|

Universal free schools meals through the Community Eligibility Provision: Maryland food service provider perspectives

Abstract: `Since 2014, the Community Eligibility Provision (CEP) school meal funding option has enabled high-poverty schools nationwide to serve universal free breakfast and lunch. Evidence suggests that CEP has benefits for student meal participation, behavior, and academic performance. This qualitative study explores perspectives among food service staff (n=28) in CEP-participating school districts in Maryland on (1) implementation barriers, (2) implementation best practices, and (3) impacts on students, school operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Further, they quantified that 15,000 hours per year statewide are spent organizing paperwork associated with eligibility determination and collecting payment for unpaid meals, information which will be helpful in decision‐making regarding HSMFA and is often difficult to obtain. Similar to previous reports, 35 Utah school foodservice directors reported that providing HSMFA does not increase labor hours. While not reported by Utah foodservice personnel, Maryland foodservice personnel report that students spend less time in line because PIN numbers and money do not need to be collected, and that overall morale is improved among foodservice personnel, students, and school employees 35 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Further, they quantified that 15,000 hours per year statewide are spent organizing paperwork associated with eligibility determination and collecting payment for unpaid meals, information which will be helpful in decision‐making regarding HSMFA and is often difficult to obtain. Similar to previous reports, 35 Utah school foodservice directors reported that providing HSMFA does not increase labor hours. While not reported by Utah foodservice personnel, Maryland foodservice personnel report that students spend less time in line because PIN numbers and money do not need to be collected, and that overall morale is improved among foodservice personnel, students, and school employees 35 .…”
Section: Discussionsupporting
confidence: 86%
“…Similar to previous reports, 35 Utah school foodservice directors reported that providing HSMFA does not increase labor hours. While not reported by Utah foodservice personnel, Maryland foodservice personnel report that students spend less time in line because PIN numbers and money do not need to be collected, and that overall morale is improved among foodservice personnel, students, and school employees 35 . Finally, several Utah foodservice directors suggested other alternatives, such as removing the reduced‐price category (and approving those students for free meals) if full funding for HSMFA does not become available.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the current study, concerns were mainly from teachers/administrators regarding quality of food and a lack of high-protein options. These concerns are highly prevalent in other recent research with food service providers ( 37 ) and are linked to the reimbursement amount received for breakfast served which limit the procurement of high protein options (i.e., breakfast sandwiches) given the greater expense and preparation requirements for these foods. The United States Department of Agriculture (USDA) has recently increased reimbursement amounts for school breakfast and lunch ( 38 ) which may help to increase higher value options served at breakfast.…”
Section: Discussionmentioning
confidence: 99%